Optimization Balongganggang Reservoir Capacity for Irrigation - Nastasia Margini; Asyraf Kamilul Basyar (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
Indonesian agriculture is the largest economic contributor after the non-oil and gas industry. However, ensuring stability in agriculture poses a significant challenge, as indicated by BPS data in 2020 and 2022, showing a decrease in the rice sector in crop area and productivity value by 2.3%. Therefore, this research aimed to increase agricultural output by optimizing planting patterns and reservoirs in Balongganggang Irrigation Area and Reservoir, Sukodadi District, Lamongan Regency, East Java. Optimization of planting patterns was carried out using rainfall and climatology data from 2013 – 2022, with a linear programming method, facilitated by POM-QM for Windows V5 program. The process of optimization focused on two objectives, namely considering maximum land area and maximizing profit. According to the analysis, optimization based on land area and profit provided the same optimal value, leading to a 9.98% increase in planting intensity from 120.57% to 130.55%, with a profit of Rp 33,967,000,000.00.